'Activating' those that 'lag behind': space-time politics in Dutch parenting training for migrants. (1st January 2016) - Van den Berg, Marguerite
ABSTRACT: Space and time (or rather space-time ) are crucial concepts in the legitimation of policy interventions into citizens' private lives. Across Europe, social policy measures to promote 'activation' among migrant communities—employment guidance, parenting training, youth work and so on—have proliferated, aiming to 'move' the Other into the here-and-now of European modernity. Van den Berg brings together theories of space-time, alterity and 'cultural lag logics' in an analysis of a contemporary case of such a policy: parenting training in the Netherlands. Based on ethnographic research, her study shows how certain societal problems are translated into problems of difference, and how that difference is in turn conceptualized as distance in space and time to be overcome through professional intervention.